2002
DOI: 10.1086/345721
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Variation in Tandem Repeats in the Intron of the Major Surface Glycoprotein Expression Site of the Human Form ofPneumocystis carinii

Abstract: Variation in the tandem repeats in the expression site of the human-derived Pneumocystis carinii major surface glycoprotein gene was characterized by denaturing gel electrophoresis. The number of repeats in 147 isolates ranged from 2 to 6, with 2, 3, and 4 repeats being the most common. Sequence analysis identified 3 types of repeat units that differed by 1 nucleotide, which suggests a hierarchy of evolution of human-derived P. carinii. Examination of sequential samples obtained from 6 patients at an interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 22 publications
1
48
0
Order By: Relevance
“…However, we observed different genotypes in BALF and sputum samples taken from one patient during an episode of PCP. In a study by Ma et al (2002), genotype differences were observed in the upstreamconserved sequence (UCS) repeat region as well as in the mt LSU rRNA gene between sputum and BALF samples or between right and left lung BALF obtained from the same patient. This finding supports the hypothesis of heterogeneity and compartmentalization of P. jirovecii genotypes within the lungs (Helweg-Larsen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, we observed different genotypes in BALF and sputum samples taken from one patient during an episode of PCP. In a study by Ma et al (2002), genotype differences were observed in the upstreamconserved sequence (UCS) repeat region as well as in the mt LSU rRNA gene between sputum and BALF samples or between right and left lung BALF obtained from the same patient. This finding supports the hypothesis of heterogeneity and compartmentalization of P. jirovecii genotypes within the lungs (Helweg-Larsen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The detection of the novel tandem repeat pattern (2, 2, 3, 3) was an interesting result. As reported in another study, most P. jirovecii strains contain three or four repeats (Ma et al, 2002;Esteves et al, 2009).…”
Section: Discussionmentioning
confidence: 63%
“…The capillary electrophoresis method offers highresolution of DNA fragments by size, allowing an easy interpretation of the results and detection of a minor population in mixed populations. The presence of multiple repeat patterns in a single clinical sample was also confirmed by denaturing gel electrophoresis analysis (Ma et al, 2002).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Therefore, it would appear that the predominant CRJE allele has two copies of the 12 bp sequence, and that the 3-copy allele is a natural variant rather than a PCR artifact. Variation of this sort has been seen in the expression sites of other species of Pneumocystis (Sunkin and Stringer, 1996;Ma et al, 2002). Transition mutations were also observed within the P. murina CRJE, but these were very rare, generally occurring in only one sequence out of 84.…”
Section: Mapping the Downstream Border Of The Crje And Assessment Of mentioning
confidence: 88%